PENILAIAN ROHANI DAN EPISTEMOLOGI PNEUMATIKOI (1KOR. 2:15) - Nggadas, Deky Hidnas Yan (STT-RAI Batam, 2025)
Previous studies on the theme of wisdom in 1 Corinthians 1:17–2:16 have tended to focus on elaborating on its background in the Greco-Roman world. However, in the most recent study published by Christian Cordona, the theme of wisdom is discussed in relation to Paul's epistemology. Unfortunately, this important study does not provide a specific review of the epistemological elements implied by 1 Corinthians 2:15. Therefore, this study aims to see the concept of the spiritual man not referring to a spiritual elite group within the congregation, but encompassing the entire community of believers living under the guidance of the Spirit of God. And this study uses an exegetical approach. The author argues that the idea of spiritual judgment and Paul's epistemology can be built specifically, without ignoring the entire context, based on 1 Corinthians 2:15. From this text we can discuss four aspects of Paul's epistemology, namely: (a) the source or basis of knowledge; (b) the nature of knowledge; (c) the medium or means or method of knowledge; and (d) the scope of knowledge. The author summarizes these epistemological elements with the term pneumatikoi epistemology.